A preliminary investigation into the factors impacting tyre failure in wheelchair basketball - Kapoor, R.; Espinosa, H.; Rowlands, D. (Proceedings of the 10th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2022)
Wheelchair sports are increasingly gaining popularity amongst athletes and spectators alike. This report outlines work carried out investigating the physical influences on the equipment used for Wheelchair Basketball. The preliminary experimental study explores the degradation of wheelchair tyres through the analysis of temperature, inflation pressure, acceleration, gameplay, individual playstyle, and strategy. With the aid of pressure monitoring and inertial measurement technology the study investigated the impact of player action on the wheelchairs. The experimental study was carried out in two phases employing the first phase of testing to provide the basis of the second phase. Through the first phase it was observed that the different temperature modalities did not have a significant impact on the degradation. The second phase focused on pressure observations and inertial sensor data paired with video. Through this process, the effect of player action was observed to have the gre atest impact on the tyre degradation. Aggressive playstyles characterised by heavy impacts, and sharp decelerations were shown to play a significant role in reducing equipment reliability.